“The Umbilical Fat Sign”: An Important and Consistent Landmark during Single Port/Incision Laparoscopic Surgery and Standard Laparoscopy - Slater, Bethany J.; Pimpalwar, Ashwin (European Journal of Pediatric Surgery, 2013)
Introduction During single port laparoscopic surgery (SPLS), access is obtained through the umbilicus and the scar is hidden within the scar of the umbilicus for providing good cosmesis. It is essential that the incision be well planned so as to get the maximum exposure through the umbilical incision. The umbilical fat sign is an important landmark to achieve this.Purpose The aim of this study is to retrospectively review importance of the umbilical fat sign as a landmark for peritoneal access during SPLS in children.Method A retrospective chart review of 57 children (33 males and 24 females) who underwent single port access surgery at Texas Children's Hospital from April 2009 to December 2010 was conducted. The median age of the patients was 10.8 years, ranging from 4 to 17 years.Technique The limits of the umbilicus were marked using a marking pen. A vertical incision is made through the center of the umbilical scar. It is of vital importance to maintain the incision in the exact center of the scar tissue. Skiving away from the center makes the entry in the peritoneal cavity harder and prolongs peritoneal access time. During all the single port cases, we have done so far we have noted that if we are in the center of the scar then we always see a blob of fat (”umbilical fat” sign) in the center. If we use a probe or grooved director through this fat direct access is obtained in the peritoneal cavity. Incision can then be extended on both sides and be kept to the limits of the umbilical ring. Peritoneal access can be obtained in 1 to 2 minutes using this approach. Umbilical reconstruction is the best performed with this approach.Results One child developed signs of wound infection and was treated successfully with antibiotics for 5 days. Scars healed well in all cases with no wound dehiscence. No umbilical scars were visible at follow-up (3 to 4 weeks postoperatively).Conclusion Umbilical fat sign is an important landmark for surgeons during SPLS for direct and quick peritoneal access and better reconstruction of the umbilicus.
Keywords: umbilicus; laparoscopy; children; single port laparoscopy; single incision laparoscopic surgery; umbilical access